Experimental and numerical assessment of new precast concrete connections under bending loads. (1st June 2020) - Baghdadi, Abtin; Heristchian, Mahmoud; Ledderose, Lukas; Kloft, Harald
Highlights: The studies propose new geometries of connections to be used in precast concrete structures. Novel concrete dry connections, can be practically used in precast structures with minimum labour, skills and time. The analyses revealed that, some geometries perform 85% of the intact section's bending capacity. Abstract: The sections of the precast concrete building elements are, most of the times, weakened due to 'cut-offs', for their pleasant appearance and easy dry jointing at construction sites. This paper experimentally and numerically evaluates the bending strength of nine precast concrete dry joints, interconnected as 'beam-to-beam' and/or 'beam-to-column' connections. The intricate geometries of the tested specimens-inspired by improved carpentry, or even wooden puzzles-were made with reinforced self-compacting Ultra-High Performance Fibre Reinforced Concrete (UHPFRC), cast in formworks manufactured by a 3 D plastic printer. Post-tensioning was, also, applied to these concrete sections, for further amplification of the performance of the elements. Then, the specimens were subjected to bending loads under the load test machine, and the load–displacement measurements were correlated with the results of the numerical models. It was concluded that, certain beam connections could produce up to 85% strength of the respective intact sections.